Survival in 31 670 patients with thin melanomas: a Swedish population‐based study. (1st January 2021) - Isaksson, K.; Mikiver, R.; Eriksson, H.; Lapins, J.; Nielsen, K.; Ingvar, C.; Lyth, J.
Summary: Background: The incidence of cutaneous malignant melanoma (CMM) continues to increase in most countries worldwide and the majority are diagnosed with thin tumours (≤ 1 mm). Objectives: The aim of the present study was to investigate the melanoma‐specific survival (MSS) as well as conditional MSS (CMSS) in patients with thin CMM in Sweden. Patients and methods: Clinical and histological parameters were obtained from the Swedish Melanoma Registry for patients diagnosed with thin CMM between 1990 and 2017. Patients were followed until the end of 2017. MSS as well as CMSS for different thickness groups were calculated using the Kaplan–Meier method and Cox regression analyses were used to calculate for survival differences between thickness groups. Results: There were 31 670 patients included for final analyses. The overall 10‐ and 20‐year MSS for thin CMMs was 97% [95% confidence interval (CI) 97–97] and 95% (95% CI 95–96), respectively. From 0·7 mm and above, MSS decreased significantly with increasing thickness level. All thickness groups had an increased survival over time. The lowest CMSS was confirmed for men with 1·0 mm in thickness but their 10‐year CMSS increased steadily over time. Women had overall better MSS as well as CMSS than men. However, the relation between MSS and CMSS was similar for both sexes. Conclusions: MSS was confirmed as excellent for patients with thin CMMs in Sweden. Although we could show a decreased MSS for patients with 0·7 mm thickness and above, the long‐term survival and, in addition, a very favourable CMSS for those patients do not support more extended follow‐up programmes than the current recommendations in Sweden.